The frequency of IgG subclass deficiency in children with recurrent respiratory infections - Güneşer, Seval; Antmen, Bülent; Altıntaş, Derya; Yılmaz, Mustafa (The Turkish Journal of Pediatrics, 1996)
We studied the frequency of IgG subclass deficiency in 61 children (ages 1-7 years, mean 3.8 years) with recurrent respiratory tract infections by using the radial immunodiffusion method. The overall frequency of IgG subclass deficiency was found to be 39.3 percent (24 patients). Among 26 children who had major immunoglobulin abnormalities, we found IgG subclass deficiency in 11 patients (42.3%). In children with normal immunoglobulin levels, the frequency of IgG subclass deficiency was 37.1 percent (13 patients).